Peran Mental Accounting dalam Memediasi Pengaruh Bias Kognitif terhadap Keputusan Penggunaan BNPL di Kalangan Mahasiswa - Dewi Puspitaningsih; Ninis Umnastuti; Nuri Purwanto (Universitas Katolik Darma Cendika, 2026)
The rapid expansion of Financial Technology (FinTech), particularly Buy Now Pay Later (BNPL) services, has transformed consumer behavior among university students. However, this convenience often leads to suboptimal financial decisions due to cognitive biases and mental accounting practices. This study aims to empirically examine the role of mental accounting in mediating the effect of cognitive bias on BNPL usage decisions among students. A quantitative approach with a causal explanatory design was employed, involving student respondents in Jombang Regency selected through convenience sampling. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS 4. The results indicate that cognitive bias has a positive and significant effect on mental accounting, and mental accounting positively and significantly affects BNPL usage decisions. However, cognitive bias does not have a significant direct effect on BNPL usage decisions. Importantly, mental accounting is found to fully mediate the relationship between cognitive bias and BNPL usage decisions. These findings confirm that mental accounting serves as a key psychological mechanism that translates cognitive distortions into consumptive behavior within the digital financial ecosystem. This study contributes to behavioral finance literature and offers practical implications for enhancing financial literacy programs and designing more responsible BNPL features for young consumers.